Attitudes of High-Level Female Sprinters Towards Factors Influencing the Training System (Baltic Journal of Sport and Health Sciences, 2016)
Background. Research conducted in the field of sports science  has supported the idea that training high-level sprinters is a consistent process, covering development of not only physical abilities (Bompa & Haff, 2009), but also a consistent personal development through the means of sports-related activity. For many years the prevalent opinion has claimed that success most often depends on the level of athletes’ physical and tactical training; however, growing  competition  among  the  athletes  calls  for  a  deeper  analysis  and  empirical  substantiation  in  relation  to factors influencing athlete training. Qualitative research results have demonstrated that high-level female sprinters prioritize athletic and technical training; however, there is a lack of attention to psychological, tactical and theory-based preparation. Obtained results have revealed that female runners are best motivated to excel, improve their performance by the external (cash prizes) rather than internal factors, the coach’s authority also plays a significantly high role. The aim of research was to discuss factors, influencing the training system of high-level female sprinters.Methods. Conducted qualitative research employed the semi-structured interview method. During the period from January to June of 2015, a total number of 20 best Lithuanian high-performance female sprinters of all time, dominating at the top of the World’s and Europe’s ratings, were interviewed. Results. The obtained research results have demonstrated that in the course of their training process runners fail to concentrate on a significant component of their training – mental training, whereas athletic and technical training, according to the respondents, is integral, thus is a priority element of the sports-related training process. It was also revealed that high-performance female sprinters were far more motivated to excel and improve their results by the external rather than the internal factors. During the interview, the respondents mostly specified being satisfied with a reward, i.e. prizes, but not honour to represent the country, or despite the reward, willingness to improve their results. Personality of the coach is also a key component in the sports-related training among high-performance female sprinters. Data obtained during the interview showed that the coach was considered not only as a specialist, but also an integral part of the training process valued for the personal qualities, such as sincerity, friendliness, ability to motivate and encourage. Conclusions.  High-performance  female  sprinters  fail  to  focus  on  a  significant  component  of  sports-related training process – psychological training. The results have demonstrated that the external factors rather than the internal ones influence their sports-related training and improvement of results. The coach is considered to be an integral part of the sports-related training process.Keywords:  high-performance, female sprinters, training system.